FUNGSI SOSIAL BANK SYARIAH - Prehantoro Prehantoro (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2010)
Bank syariah salah satu tujuannya ialah profit oriented sebagai intermediary finansial institution di samping sebagai lembaga baitul maal Bank syariah bisa menerima dana yang berasal dari zakat, infak, sedekah, hibah, atau dana sosial lainnya yang diantaranya berasal ta’zir. Bank syariah juga menyalurkannya dana sosial yang berasal dari wakaf uang kepada pengelola wakaf (nadzir) sesuai dengan kehendak pemberi wakaf (wakif). Pelaksanaan fungsi sosial harus sesuai dengan ketentuan UU Pengelolaan Zakat dan UU Wakaf.Bank of Moslem law one of its target is profit oriented as financial institution intermediasi beside as institute of baitul maal. Bank of Moslem law can accept the fund coming from zakat , infak, alms, hibah, or other social fund which among other things come the ta’zir. Bank of Moslem law also channel it social fund coming from communal ownership of money to communal ownership organizer (nadzir) as according to will ;desire of communal ownership giver (wakif). social Function execution have to pursuant to Statute of Management of Zakat and Statute of Wakaf.